2018
DOI: 10.1080/1533256x.2018.1450264
|View full text |Cite
|
Sign up to set email alerts
|

Appalachian Women’s Use of Substance Abuse Treatment: Examining the Behavioral Model for Vulnerable Populations

Abstract: The Gelberg-Andersen Behavioral Model for Vulnerable Populations was applied to understand vulnerable Appalachian women’s (N = 400) utilization of addiction treatment. A secondary data analyses included multiple multivariate analyses. Strongest correlates of treatment utilization included ever injecting drugs (OR = 2.77), limited availability of substance abuse treatment facilities (OR = 2.03), and invalidated violence abuse claims (OR = 2.12). This study contributes theory-driven research to the greater socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 63 publications
1
8
0
Order By: Relevance
“…This difficulty is exacerbated by the lack of public transportation infrastructure in most areas of the Appalachian region. This finding is consistent with other results indicating that when fewer substance abuse treatment facilities are accessible to Appalachian women, they will be less likely to use treatment services at all [50], and a study conducted by LeGrow et al (2007), which showed that Appalachian residents who reported transportation problems also described difficulty accessing healthcare [51]. Similarly, others have found that residents of rural communities utilize healthcare services more when they have access to a form of transportation, such as possessing a driver's license or having transportation through a friend or family member [52].…”
Section: Availability and Accommodationsupporting
confidence: 92%
“…This difficulty is exacerbated by the lack of public transportation infrastructure in most areas of the Appalachian region. This finding is consistent with other results indicating that when fewer substance abuse treatment facilities are accessible to Appalachian women, they will be less likely to use treatment services at all [50], and a study conducted by LeGrow et al (2007), which showed that Appalachian residents who reported transportation problems also described difficulty accessing healthcare [51]. Similarly, others have found that residents of rural communities utilize healthcare services more when they have access to a form of transportation, such as possessing a driver's license or having transportation through a friend or family member [52].…”
Section: Availability and Accommodationsupporting
confidence: 92%
“…A greater number of days a participant engaged in illegal activity for profit was the strongest correlate to violent victimization, which is a finding that is corroborated by past research involving justice-involved individuals in rural Kentucky (Oser et al, 2009). Rural residents might have extensive histories of arrest and illegal activity because of their undertreated or untreated behavioral health concerns-including substance use disorders (SUD)-which may adversely affect employment (T. Browne et al, 2016;Conger, 1997;Victor et al, 2018;Warner & Leukefeld, 2001). To that end, using sex in exchange for money and drugs was also a strong correlate of violent victimization.…”
Section: Economic-compulsive Violence Victimizationmentioning
confidence: 63%
“…Given the high prevalence of NMPOU among the current sample, it is recommended that MAT treatment access be expanded in rural jail sites, as it may also have implications for their future risk of violent victimization and recidivism (Surratt et al, 2018). Challenges related to treatment engagement and recidivism may be present if discharge planning inadequately connects participants to the appropriate services experiencing ongoing victimization (Snell-Rood, Staton-Tindall, et al, 2016;Victor et al, 2018). Considering Appalachian Kentucky, gender-responsive peer supports should ideally be familiar with the cultural norms and the needs of women that are unique to the region (Covington et al, 2008;Najavits, 2007;Schumacher & Holt, 2012).…”
Section: Recommendations For Practicementioning
confidence: 99%
See 1 more Smart Citation
“…The framework builds upon the original Behavioral Model developed in the 1960s by expanding on “Traditional” individual-level factors to include predictors related to vulnerability [ 40 , 46 ]. These are further organized into: (i) “Predisposing Vulnerable” factors, which include characteristics that may occur prior to disease onset and that are related to social structure such as immigration status, gender, living conditions, and victimization; (ii) “Enabling Vulnerable” factors, which are those individual- and community-based factors that may facilitate or impede health services utilization and include competing needs, social support, coping mechanisms, and availability of services, and; (iii) a “Need Vulnerable” domain which includes perceived and confirmed health needs related to vulnerability such as STIs, tuberculosis, and substance use disorders [ 40 , 44 46 ]. These three major headings were applied to our data and subsequently adapted into a conceptual framework that further distinguishes between structural and sociocultural predisposing health determinants, delineates relationships, and guides pathways for potential interventions.…”
Section: Methodsmentioning
confidence: 99%